Cytokines regulating the innate response - O’Garra, Anne (Henry Stewart Talks, 2009)
Th1 and Th2 cells in immune regulation, Th1 and Th2 differentiation, Intracellular pathogens, Cytokines regulate the development of Th1 and Th2, IL-12 and Th1 responses are required for resistance to mycobacterial infections, MTb infections in humans, The IL-12 family, IL-23, TGF-beta, Inflammation is required to eradicate pathogens but can lead to host damage, IL-10 production and implications for function of the immune response, Cytokines limit immunopathology: a penalty is chronic infectious disease